Synthesis of Polysulfone Based Amphiphilic Graft Copolymers by a ‘Grafting to’ Approach - Çiftçi, Mustafa (My University, 2019)
Synthesis of amphiphilic polysulfone graft copolymers by ‘‘Click’’ chemistry is described. First, a commercial PSU was chloromethylated to give chloro-funtional PSU (PSU-Cl). Subsequently, chloride groups were converted into azide moieties by nucleophilic substitution. Hydrophilic poly(N,Ndimethylacrylamide) (PDMA) side chains were then attached via a “grafting to” approach by using coppercatalyzed azide–alkyne cycloaddition (CuAAC). Precursor polymer and the final amphiphilic copolymers were characterized by proton nuclear magnetic resonance ( 1H NMR), fourier-transform infrared spectroscopy (FT-IR), gel permeation chromatography (GPC) and contact angle measurements.
Keywords: [No Keywords]